Armando Four-Wheel Patrol Management Optimization of Satuan Samapta to Prevent Robbery in the Kudus Police Jurisdiction - Pratama, Armando Satya Putra (Advances in Police Science Research Journal, 2024)
The goal of this study is to answer the writer's problem of why Satuan Samapta's patrol to prevent robbery wasn't optimal. In this research, the writer will describe the human resource and patrol method of a four-wheel patrol to prevent a robbery in Kudus police jurisdiction. This study uses a qualitative approach. Data gathered by the writer has descriptive characteristics so the writer uses interviews, observation, and documentary studies as data-gathering technic. The focus of this research is the management of Satuan Samapta’s four-wheel patrol in Kudus police especially in Unit Turjawali. Primary data was gathered by doing interviews with 10 people and secondary data was gathered by scripts. Data validation uses source, method, and theory triangulation. The results of this study indicate that the management of four-wheel patrol analyzed with management element theory, competence theory, management function theory, Perkabaharkam No. 1 Tahun 2017, Perpol No. 2 Tahun 2021 was not optimal. The human resources have a lack of quantity and quality, as well as a less precise method that causes Satuan Samapta’s four-wheel patrol to prevent a robbery in Kudus police, wasn’t optimal.